Investigation of mechanical properties of synthesized AA2024-T351/SiO2 metal matrix nano-composite. (2020) - Singh, Bharat; Chandel, Siddharth; Singhal, Piyush
Abstract: Metal matrix nano composites (MMNCs) have vital role in the field of industrial applications due to its light weight with improved mechanical properties in terms of hardness, tensile strength and having good wear resistance. Aluminium, magnesium and copper have been mostly used to develop nanocomposites injecting the common reinforcing agents such as ceramics particles, carbide, oxide and nitride forms of metals or non-metals. In present work, AA2024-T351 as base metal matrix reinforced with silicon di-oxide (SiO2 ) nanoparticles having particles size of 30 nm with varying weight percentage. Stir casting method is adapted to get homogeneity in the mixture during synthesis of metal matrix nanocomposite (MMNC). The improved mechanical properties of fabricated metal matrix nano-composites are examined and compared with the base metal.